Detroit School Reform in Comparative Contexts Community Action Overcoming Policy Barriers - St. John, Edward; Girmay, Feven; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book critically examines how the narrative of global economic competition was used to rationalize college preparatory curriculum for all high school students and promote charter schools in Detroit. Using mixed qualitative and quantitative methods, the study identifies neighborhood risk factors undermining students' academic success, along with the positive effects of churches and service centers as mitigating forces. The authors focus on a range of topics and issues including market competition, urban decline, community resources, testing and accountability, smaller schools, and engaged learning. The volume illustrates how action studies by engaged scholars working with community activists empowers students to overcome emerging barriers.
Series Foreword -- Foreword -- Acknowledgements -- Contents -- Lists of Tables, Figures, and Maps -- Chapter 1: Introduction -- Part 1: Policy Failures Creating Barriers to Student Success -- Chapter 2: Economic Competitiveness -- Chapter 3: Educational Policy -- Chapter 4: Market Competition -- Part II: Neighborhood Risks, Resources, and College Preparation -- Chapter 5: Neighborhood Risks -- Chapter 6: Community Resources -- Chapter 7: High-School & College Preparation -- Part III: Community Action Addressing Barriers to Student Success -- Chapter 8: Student Encouragement -- Chapter 9: Engaged Learning -- Chapter 10: Conclusion -- Authors and Research Associates -- Endnotes -- References. .
Keywords: Sociology, Urban; Education and state; Educational sociology; Urban economics; Urban Sociology; Education Policy; Sociology of Education; Urban Economics